Enhancing Onion Supply Chain Using The Smart Contract Platform: A Meta-Analysis - Kenneth L. Armas; Bren C. Bondoc; Rhea Lyn La Penia (Journal of Applied Engineering and Technological Science (JAETS), 2023)
In the ever-evolving landscape of global agricultural supply chains, ensuring traceability, transparency, and sustainability is paramount to guaranteeing food safety, combating fraud, and meeting consumer demands. The Philippine onion industry, a vital component of the nation's horticultural sector, grapples with challenges related to traceability and transparency that impact customer trust and economic sustainability. While the adoption of smart contract platforms has revolutionized traceability and transparency in various agricultural sectors worldwide, their potential in the Philippine onion market remains underutilized. This study employs a comprehensive meta-analysis approach to evaluate the existing traceability and transparency mechanisms within the Philippine onion industry, drawing insights from a diverse set of studies. The meta-analysis reveals a consistently positive impact of these mechanisms on traceability and transparency. The findings, supported by a range of studies, underscore the value of these mechanisms in improving product quality, supply chain efficiency, and transparency. The study further investigates the potential impact of smart contract platforms in enhancing traceability and transparency throughout the onion industry's supply chain. Meta-analysis results suggest that the adoption of smart contract platforms holds promise in furthering these objectives. Through automated record-keeping and real-time data sharing, smart contracts have the potential to address existing challenges related to data fragmentation and limited technological integration. Identifying barriers to smart contract platform adoption in the context of traceability and transparency, the study proposes a set of strategic initiatives and recommendations. These recommendations cater to various stakeholders, including government bodies, academic institutions, local authorities, onion farmers, and industry players, aiming to promote the widespread adoption of smart contract platforms. This study extends beyond the confines of the Philippine onion industry, offering valuable insights into the role of smart contract platforms in enhancing traceability, transparency, and sustainability within agricultural supply chains. As the world works towards achieving the Sustainable Development Goals of the United Nations, this research contributes to the realization of "Zero Hunger" and "Responsible Consumption and Production" by promoting transparent and sustainable supply chains. By bridging the gap in understanding the potential of smart contract platforms in enhancing traceability and transparency, this study paves the way for innovative solutions, inspiring trust, and fostering sustainable farming practices within the onion industry and, potentially, in similar sectors worldwide.